Éléments pour une histoire de l’éducation à la citoyenneté : de l’école publique française au lycée, quels enjeux ? - Céline Chauvigné; Richard Étienne; Loïc Clavier (Recherches en Éducation)
Citizenship education mirrors our society, grappling with social, political, and economic fluctuations of the period. From 19th century civic and moral instruction on behalf of the State, to the democratic individualism of recent years, citizenship has mirrored the tensions of society that permeate school.The role of citizenship at school and in society and the issues that are at stake are in constant upheaval. They encompass four periods that this article will attempt to highlight, thus outlining the broad conceptions and implementations of citizenship into schools, in its complexity and its precariousness.